Coastal Tourism in Maine - Lyons, Steve (Maine Policy Review, 2023)
Tourism is an important industry in Maine. Its heritage stretches back nearly 200 years and it continues to be an economic driver today. This commentary describes the economic impact of tourism on Maine's coastal regions.
Keywords: Downeast; Maine beaches; Acadia Region; Maine midcoast